2003
DOI: 10.1023/a:1022905618883
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Negotiation of the cervix, the use of a volsellum, and the presence of blood on the catheter wall or on the cervix do not affect the results. Changing the catheter and blood on the catheter tip significantly diminish the pregnancy and implantation rates. Soft catheters perform better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In contrast, Sallam et al ( 18 ) evaluated 784 IVF cycles, including 655 IVF-ICSI treatments, and found that negotiation of the cervix, the use of a vulsellum, and the presence of blood on the catheter wall or cervix did not affect CPR. Neithard et al ( 11 ) reported that ET performed with afterloading external guidance increased pregnancy rates when compared with difficult ETs, but this increase did not reach a statistically significant level in their retrospective evaluation of 127 IVF-ICSI cycles.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, Sallam et al ( 18 ) evaluated 784 IVF cycles, including 655 IVF-ICSI treatments, and found that negotiation of the cervix, the use of a vulsellum, and the presence of blood on the catheter wall or cervix did not affect CPR. Neithard et al ( 11 ) reported that ET performed with afterloading external guidance increased pregnancy rates when compared with difficult ETs, but this increase did not reach a statistically significant level in their retrospective evaluation of 127 IVF-ICSI cycles.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is similar to study by Sallam et al . [12] in which blood at catheter tip was associated with reduced pregnancy rates. However, no difference was seen when transfer was difficult or extra manipulation like use of volsellum or cervical dilation was required.…”
Section: Discussionmentioning
confidence: 99%
“…As such, ICSI-AOA is an important approach in terms of offering the potential for a biological child, not least for patients whose religious beliefs do not permit sperm donation. 59 In these circumstances, AOA with calcium ionophore treatment after ICSI results in a statistically significant improvement in fertilization (105 cycles; 65.2–68.8% fertilization following ionophore AOA; p = 0.008), as well as clinical pregnancy (23.5–25.0%) and live birth rates (LBRs). 53 Nonetheless, patient selection is key, and is probably the biggest challenge to application of AOA as a treatment add-on, particularly given the absence of clinically validated and accessible diagnostic assays for PLCζ.…”
Section: Calcium Ionophorementioning
confidence: 99%